Strategi Media Lokal di Era Pasca Pandemi: Studi Kasus Harian Bhirawa di Surabaya (Jurnal Kajian Media, 2022)
The impacts of Covid-19 Pandemic seems not only ruin the various joints of human lie. But also it has an impact on the life of the mass media industry. Both print media, online media and electronica media (radio and television). Not a few media that were forced to “lay off” their employees and forced to out of bussiness. This research aims to determine how Harian Bhirawa’s strategic, a local media in Surabaya, be able to survive in Covid-19 Post Pandemic Era. This qulitative research was conducted through a case study, with a media organizing management perspective, specifically techniques, programs, marketing and human resources. The results of this research indicates, that Harian Bhirawa is able to elaborate the marketing and human resources divisions to partner and to get financial benefits from Goverment of East Java Province. As part of the mass media that should adapts to advances in information technology (technorealist), Harian Bhirawa is able to survive without having to “sacrifice” its criticality, and is able to act as a media of education (to educate), information (to infrom), and entertaiment (to intertaint) Key Words : Media strategic, case study, bhirawa daily, media organizing management